Study on the mechanical properties of the nanoconcrete using nano-TiO2 and nanoclay. (2022) - Anitha Selvasofia, S.D.; Sarojini, E.; Moulica, G.; Thomas, Sajin; Tharani, M.; Saravanakumar, P.T.; Manoj Kumar, P.
Abstract: Nano modified concretes have become the attractive research area now-a-days. It was anticipated that the inclusion of appropriate nano-sized particles would enhance the mechanical properties of the concrete. Though the capability of nano-TiO2 particles in improving the mechanical strength of the base material was documented in the earlier studies, their influence on the concrete was not yet dealt properly. The current study is attempting to enhance the mechanical properties of the concrete using small mass fraction of nano-TiO2 particles as cement substitute and nanoclay as the fine aggregate substitute. The initial tests were accompanied on the concrete, only with different fraction of nano-TiO2 particles to identify the best nano-TiO2 proportions for different curing periods (7 days, 28 days and 60 days). Then, the secondary tests were piloted with varying mass fractions of nanoclay with the identified best proportion of the nanoconcrete. The results revealed that 2.0% nano-TiO2 particles and 3.0% nanoclay were the optical fractions in the nanoconcrete to obtain maximum values of split tensile, compressive, and flexure strengths. The improvement in the mechanical properties of the concrete was attained about 30% with the help of nano-TiO2 particles and nanoclay.